‘Where the F… is Vuotso?’ : heritage of Second World War forced movement and destruction in a Sámi reindeer herding community in Finnish Lapland - Seitsonen, Oula; Koskinen-Koivisto, Eerika (International Journal of Heritage Studies, 2018)
In this paper we discuss the heritage of the WWII evacuation and the so-called ‘burning of Lapland’ within a Sámi reindeer herding community, and assess how these wartime experiences have moulded, and continue to mould, the ways people memorialise and engage with the WWII material remains. Our focus is on the village of Vuotso, which is home to the southernmost Sámi community in Finland. The Nazi German troops established a large military base there in 1941, and the Germans and the villagers lived as close neighbours for several years. In 1944 the villagers were evacuated before the outbreak of the Finno-German ‘Lapland War’ of 1944–1945, in which the German troops annihilated their military installations and the civilian infrastructure. Today the ruins of demolished German military installations persist around the village as vivid reminders, and act for the villagers as important active agents in memorising this vital phase in Lapland’s recent past. They also appear to facilitate nostalgia for the more independent days before traditional Sámi lifeways were ruptured by stronger Finnish State intervention in the post-war decades. peerReviewed